The use of life-saving extracorporeal membrane oxygenation (ECMO) for pregnant woman with status asthmaticus. (2nd January 2017) - Steinack, Carolin; Lenherr, Renato; Hendra, Heidy; Franzen, Daniel
ABSTRACT: Introduction: Status asthmaticus can develop into a life-threatening disorder that requires mechanical ventilation. Severe respiratory failure during pregnancy can worsen maternal and fetal outcomes. Previous case studies have demonstrated extracorporeal membrane oxygenation (ECMO) as a life-saving measure for pregnant women with acute respiratory distress syndrome (ARDS) as well as non-pregnant patients with status asthmaticus. Case study: A 25-year-old woman, who was 5 weeks pregnant, was admitted with status asthmaticus and severe hypercapnic respiratory failure. Despite rescue therapies such as pressure control ventilation with high inspiratory pressures, inhaled beta2 agonists and antimuscarinic drugs, intravenous salbutamol, methylprednisolone and magnesium sulfate, her condition gradually deteriorated. Veno-venous ECMO was initiated for respiratory support and the patient's clinical condition as well as the gas exchange improved within the next few days. ECMO was removed and the patient was extubated after 2 days. Sonography, however, revealed a retrochorial hematoma; the patient was diagnosed with abortus imminens and successfully treated with magnesium substitution and bed rest. Finally, she gave birth to a healthy boy at 38 weeks of gestation. Conclusions: This is the first case report on the successful use of ECMO in a pregnant woman with severe respiratory insufficiency due to status asthmaticus, who failed to respond to invasive mechanical ventilation and maximum pharmacological treatment. Despite this life-threatening condition, the use of ECMO in our patient has greatly improved the chance of survival for the mother and the baby, who was born without any complications.